2003
DOI: 10.1038/sj.bjp.0705522
|View full text |Cite
|
Sign up to set email alerts
|

FK506 potentiates NGF‐induced neurite outgrowth via the Ras/Raf/MAP kinase pathway

Abstract: 1 Nerve growth factor (NGF) and other members of the neurotrophin family are critical for the survival and differentiation of neurons within the peripheral and central nervous systems. 2 Neurophilin ligands, including FK506, potentiate NGF-induced neurite outgrowth in several experimental models, although the mechanism of this potentiation is unclear. 3 Therefore, we tested which signaling pathways were involved in FK506-potentiated neurite outgrowth in SH-SY5Y neuroblastoma cells using specific pharmacologica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
47
0
3

Year Published

2006
2006
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(53 citation statements)
references
References 25 publications
(29 reference statements)
2
47
0
3
Order By: Relevance
“…17 The agent FK506 has also been shown to potentiate nerve growth factor-induced neurite outgrowth in SH-SY5Y cells, in PC12 cells, and in sensory neuronal cultures. 11,20,24 Our results indicate that FK506, cyclosporin A, and dexamethasone all can promote neurite outgrowth following thapsigargin-induced calcium challenges, and that they can do so without the presence of neurotrophins. Dexamethasone and cyclosporin A can also lessen the extent of apoptosis after thapsigargin-induced injury.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…17 The agent FK506 has also been shown to potentiate nerve growth factor-induced neurite outgrowth in SH-SY5Y cells, in PC12 cells, and in sensory neuronal cultures. 11,20,24 Our results indicate that FK506, cyclosporin A, and dexamethasone all can promote neurite outgrowth following thapsigargin-induced calcium challenges, and that they can do so without the presence of neurotrophins. Dexamethasone and cyclosporin A can also lessen the extent of apoptosis after thapsigargin-induced injury.…”
Section: Discussionmentioning
confidence: 83%
“…4), although this difference in neurite distribution did not achieve statistical significance. However, addition of 10 M dexamethasone increased the fraction of neurites whose lengths were less than or equal to 10,15,20,25,30,35,40, and 45 microns (Fig. 5) in a statistically significant fashion (p Ͻ 0.05, t-test).…”
Section: Response To Dexamethasonementioning
confidence: 99%
“…For example, FK506 potentiates NGFinduced neurite outgrowth via the Ras/Raf/MAPK pathway and involves PI3-k signaling (Price et al, 2003(Price et al, , 2005. Gold et al (1999) reported that GA blocked neurotrophic action of FK506, suggesting FK506 interaction with Hsp90 via binding to FKBP52 is important for its neuroregenerative properties.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that immunophilin ligands complement the action of neurotrophic factors and in part by enhancing the MAPK/JNK pathways (Price et al, 2003). On the other hand, earlier study has shown that JNJ460 induces neurogenesis indirectly in a Schwann cell dependent manner, but not when directly administered to PC12 cells (Birge et al, 2004).…”
Section: Discussionmentioning
confidence: 99%